A PET study of visuospatial attention - Corbetta, M (J Neurosci, 1993)
Positron emission tomography (PET) was used to identify the neural systems involved in shifting spatial attention to visual stimuli in the left or right visual field along foveofugal or foveocentric directions. Psychophysical evidence indicated that stimuli at validly cued locations were responded to faster than stimuli at invalidly cued locations. Reaction times to invalid probes were faster when they were presented in the same than in the opposite direction of an ongoing attention movement. PET evidence indicated that superior parietal and superior frontal cortex were more active when attention was shifted to peripheral locations than when maintained at the center of gaze. Both regions encoded the visual field and not the direction of an attention shift. In the right superior parietal lobe, two distinct responses were localized for attention to left and right visual field. Finally, the superior parietal region was active when peripheral locations were selected on the basis of cognitive or sensory cues independent of the execution of an overt response. The frontal region was active only when responses were made to stimuli at selected peripheral locations. These findings indicate that parietal and frontal regions control different aspects of spatial selection. The functional asymmetry in superior parietal cortex may be relevant for the pathophysiology of unilateral neglect.